1993
DOI: 10.1159/000111352
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of 2-Oxoglutarate Uptake by Synaptosomes from Bovine and Rat Retina and Cerebral Cortex and Regulation by Glutamate and Glutamine

Abstract: 2-Oxoglutarate (2-OG) is a metabolic precursor of glutamate and may be utilized to replenish the neurotransmitter pool. 2-OG is rapidly transported into neurons by a high-affinity carrier that is particularly prevalent in gluta-matergic terminals. Here we report the kinetics of [U-14C]2-OG uptake by crude synaptosomal preparations from bovine and rat retina and brain, and the modulatory effects of glutamate and glutamine. In all four tissues, 2-OG uptake was mediated by a high-affinity system (K Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…The saturation kinetics of [ 14 C]succinate and [ 14 C]citrate uptake by rat astrocytes (K t 28.4 and 1550 lM respectively) determined in the present study are in good agreement with K t values of 2-142 lM (succinate) and 220 lM (citrate), and a K i value of 2.1 mM of citrate for succinate transport, in rodent NaC3 (Chen et al 1998;Kekuda et al 1999;Pajor et al 2001). Pajor et al (2001) have cloned NaC3 from mouse brain, and have speculated that NaC3 might correspond to the NaDC previously identified in glutamatergic synaptosomes (Lehmann et al 1993). However, as shown in Table 3 and our previous reports (Inoue et al 2002b(Inoue et al , 2004, cis-inhibition experiments have revealed that NaC2 in neurons can also accept dicarboxylates such as malate, succinate and fumarate with relatively high affinity, as can NaC3 in astrocytes.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The saturation kinetics of [ 14 C]succinate and [ 14 C]citrate uptake by rat astrocytes (K t 28.4 and 1550 lM respectively) determined in the present study are in good agreement with K t values of 2-142 lM (succinate) and 220 lM (citrate), and a K i value of 2.1 mM of citrate for succinate transport, in rodent NaC3 (Chen et al 1998;Kekuda et al 1999;Pajor et al 2001). Pajor et al (2001) have cloned NaC3 from mouse brain, and have speculated that NaC3 might correspond to the NaDC previously identified in glutamatergic synaptosomes (Lehmann et al 1993). However, as shown in Table 3 and our previous reports (Inoue et al 2002b(Inoue et al , 2004, cis-inhibition experiments have revealed that NaC2 in neurons can also accept dicarboxylates such as malate, succinate and fumarate with relatively high affinity, as can NaC3 in astrocytes.…”
Section: Discussionsupporting
confidence: 89%
“…Pajor et al . (2001) have cloned NaC3 from mouse brain, and have speculated that NaC3 might correspond to the NaDC previously identified in glutamatergic synaptosomes (Lehmann et al . 1993).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…However, more substantive explanations may also pertain, including the expression of other variant forms of GLT1 not yet recognized, or other transporters, such as EAAC1 (He et al, 2000), post-translational modification, or interacting proteins interfering with antibody binding. In addition, some axon terminals may use alternate pathways to resupply excitatory terminals with glutamate (Fonnum, 1984;Shank et al, 1989;Lehmann et al, 1993;Sonnewald et al, 1993;Westergaard et al, 1995;Hertz et al, 1999;Hassel and Brathe, 2000a,b).…”
Section: Glt1 Is Expressed In a Subpopulation Of Axon Terminalsmentioning
confidence: 99%